Crustacean meal in laying hen rations. Effect on productive variables and sensory evaluation of eggs stored in different conditions - Carranco, M. Elena; Calvo, C. C.; Carrillo, D. S.; Ram?rez, C. R.; Morales, B. E.; Sangin?z, G. L.; Fuente, M. B.; ?vila, G. E.; P?rez-Gil, R. F. (Cuban Journal of Agricultural Science, 2011)
The effect of the inclusion of shrimp meal (SM) and red crab meal (RCM) on productive variables was assessed in laying hen diets. A sensorial evaluation was made in eggs, whether fresh or stored at different conditions. One-hundred and thirty-five hens were distributed in three treatments: control, SM (20 %), and RCM (4 %). The results were analyzed by ANDEVA and Friedman (P < 0.05). It was proved that productive variables, such as the sensorial evaluation, did not show significant differences between treatments up to 15 d of storage. It was concluded that, besides providing another feed alternative in poultry feeding, the incorporation of Crustacean meal did not affect the productive yield of the birds or provoked negative sensorial effects, every time the storage was not prolonged. Key words: shrimp meal, red crab meal, egg, productive variables, sensorial quality.